2012
DOI: 10.1073/pnas.1201428109
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the VirB4 ATPase, alone and bound to the core complex of a type IV secretion system

Abstract: Type IV secretion (T4S) systems mediate the transfer of proteins and DNA across the cell envelope of bacteria. These systems play important roles in bacterial pathogenesis and in horizontal transfer of antibiotic resistance. The VirB4 ATPase of the T4S system is essential for both the assembly of the system and substrate transfer. In this article, we present the crystal structure of the Cterminal domain of Thermoanaerobacter pseudethanolicus VirB4. This structure is strikingly similar to that of another T4S AT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
100
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 82 publications
(120 citation statements)
references
References 46 publications
16
100
1
Order By: Relevance
“…Importantly, its shape has similarities to that of TrwK /VirB4 in that it is also formed of three distinct layers. TrwB /VirD4 and TrwK /VirB4 have been shown to have very similar structures in spite of low sequence similarities (Wallden et al , 2012). Thus, it is not surprising that they should share similar density features (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, its shape has similarities to that of TrwK /VirB4 in that it is also formed of three distinct layers. TrwB /VirD4 and TrwK /VirB4 have been shown to have very similar structures in spite of low sequence similarities (Wallden et al , 2012). Thus, it is not surprising that they should share similar density features (Fig 4A).…”
Section: Resultsmentioning
confidence: 99%
“…VirB11 has been reported as a hexamer in different systems (Machon et al , 2002; Savvides et al , 2003; Hare et al , 2006). VirD4 and VirB4, though expected to form hexamers, have been identified in monomeric and dimeric forms as well (Gomis‐Ruth et al , 2001; Schroder et al , 2002; Rabel et al , 2003; Arechaga et al , 2008; Mihajlovic et al , 2009; Durand et al , 2011; Pena et al , 2012; Wallden et al , 2012). All three ATPases interact with one another and these interactions likely direct the two processes in which T4S systems are involved: pilus biogenesis and substrate secretion (Atmakuri et al , 2004; Ripoll‐Rozada et al , 2013).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, VirB11 may function with VirB4 to coordinate a structural change in VirB2 pilin protein and mediate VirB2 binding to other T4SS components, which in turn affects pilus polymerization (Kerr and Christie, 2010). Accumulating genetic studies and recent structural studies support a model in which VirB4 dimers or homomultimers contribute both structural information for the assembly of a trans-envelope channel competent for DNA transfer and an ATP-dependent activity for configuring this channel as a dedicated export machine (Fronzes et al, 2009a;Durand et al, 2010Durand et al, , 2011Kerr and Christie, 2010;Li et al, 2012;Pena et al, 2012;Wallden et al, 2012). In addition, the TrIP assay results showed that translocating DNA substrates first interact with the VirD4 receptor, followed by VirB11 ATPase, suggesting VirB11 may function together with VirB4 and deliver the T-DNA substrate to the transfer channel of the T4SS (Cascales and Christie, 2004a;Bhatty et al, 2013;Chandran, 2013;Christie et al, 2014).…”
Section: Transport Of T-dna and Virulence Proteins Via Type IV Secretmentioning
confidence: 99%
“…This outer-membrane core complex contains 14 copies each of VirB7, VirB9, and VirB10; and is inserted in both the inner and outer membranes (Fronzes et al, 2009a(Fronzes et al, , 2009b. The structure of the core complex is cylindrical and contains two layers, the inner (I) and outer (O) layers (Fronzes et al, 2009b;Wallden et al, 2012;Bhatty et al, 2013). Upon sensing ATP energy utilization by the VirD4 and VirB11 ATPases, the VirB10 protein conformation changes and may help regulate the O layer hole opening to allow substrate transfer through the T4SS channel (Cascales and Christie, 2004b).…”
Section: Transport Of T-dna and Virulence Proteins Via Type IV Secretmentioning
confidence: 99%
“…However, much more information regarding proteins involved in the T4S processes is available for bacteria of Gramnegative origin Kurenbach et al, 2006;Wallden et al, 2010;Clewell, 2011). Only very recently has the first structural information on Gram-positive transfer proteins become available (Porter et al, 2012;Walldé n et al, 2012).…”
Section: Introductionmentioning
confidence: 99%